Two new species of stone loaches of the genus Schistura from the Koladyne basin, Mizoram, India (Teleostei: Cobitoidei: Nemacheilidae) - Lokeshwor, Y.; Vishwanath, W. (Zootaxa, 2013)
Two new species of Schistura are described from the Koladyne basin of Mizoram, India. Schistura nebeshwari is distinguished from its congeners by the combination of the following characters: a prominent dorsal adipose crest on the caudal peduncle, 11–14 dark olivaceous bars on the body, the entire ventral surface of head with numerous small melanophores, an incomplete lateral line, three black spots at the dorsal-fin base, a complete prominent black basicaudal bar, lower jaw with a shallow median notch, and no suborbital flaps in males. Schistura scyphovecteta differs from its congeners by the combination of the following characters: six dark brown saddles, each one continuing to the flank, forming globular-shaped bars overlaying a background brown stripe along the lateral line, a complete lateral line, two black spots at the dorsal-fin base, an incomplete black basicaudal bar, no median notch on the lower jaw, and a suborbital flap present in males.